The opponent process theory of leadership succession. (November 2015) - Hollenbeck, John R.; DeRue, D. Scott; Nahrgang, Jennifer D.
Groups are increasingly conceptualized as self-regulating, adaptive social systems, where time and history play central explanatory roles. Despite this, concepts related to opponent processes, which are central to theories of self-regulation, have been absent from discussions of leadership of groups. In this paper, we introduce the opponent process theory of leadership succession, and argue that the impact of leadership on current outcomes can be fully appreciated only by complementing the understanding of the current leader's behaviors and style with the behaviors and styles of his or her predecessor. We outline both the process and content of opponent processes highlighting their potential to explain both adaptive and maladaptive behavior in groups.